Design, Synthesis, Antibacterial Evaluations and In Silico Studies of Novel Thiosemicarbazides and 1,3,4-Thiadiazoles - Sara Janowska; Dmytro Khylyuk; Sylwia Andrzejczuk; Monika Wujec (Molecules, 2022)
The emergence of drug-resistant bacterial strains continues to be one of the major challenges of medicine. For this reason, the importance of searching for novel structures of antibacterial drugs chemically different from the currently known antibiotics is still of great importance. In this study, we synthesized the thiosemicarbazide and 1,3,4-thiadiazole derivatives and tested them for antibacterial activity. In in vitro tests, we examined the activity of the synthesized substances against Gram-positive and Gram-negative bacteria strains. While all 1,3,4-thiadiazoles tested lacked significant activity, the antimicrobial response of the thiosemicarbazides was moderate and it was also dependent on the type and position of the substituent on the phenyl ring. The highest activity towards all Gram-positive bacteria strains was shown by all three linear compounds containing the trifluoromethylphenyl group in the structure. The MIC (minimum inhibitory concentration) values were in the range of 3.9–250 µg/mL. Additionally, we try to explain the mechanism of the antibacterial activity of the tested compounds using the molecular docking to DNA gyrase and topoisomerase IV, following previous reports on the molecular basis of the activity of thiosemicarbazides. Docking simulations allow the purposing dual mechanism of the antibacterial activity of the synthesized compounds through inhibition of topoisomerase IV DNA gyrase with the moderate prevalence of the topoisomerase pathway.